Exergaming With Integrated Head Turn Tasks Improves Compensatory Saccade Pattern in Some Patients With Chronic Peripheral Unilateral Vestibular Hypofunction - Swanenburg, Jaap; Büchi, Fabienne; Straumann, Dominik; Weber, Konrad P.; de Bruin, Eling D. (Frontiers in Neurology, 2020)
Background: This study aimed to determine whether vestibular rehabilitation using active video games (Exergames), including promoted head turns and unsupported locomotion, may facilitate vestibular compensation and gait in subjects with one-sided chronic peripheral vestibular hypofunction (cPVH). Methods: 12 patients with cPVH (mean age of 65 ± 12 years, 8 male) were recruited for this study. The study consisted of a four-week baseline control period T1-T2 followed by a four-week intervention period T2-T3. The intervention included exergames that required physical tasks such as steps, weight shifts or balance control to cognitive challenges, in a virtual environment to play the game. The subjects participated in a total of 176 min of exergaming in eight sessions. Because of the changing projection direction of the game to the wall, the subjects had to turn their heads constantly while playing the game. Dynamic visual acuity (DVA) was assessed. Vestibulo-Ocular reflex (VOR) gain deficit and cumulative overt saccade amplitude (COSA) were measured with the video head-impulse test. Additionally, the functional gait assessment (FGA), Extended Timed Get-Up-and-Go (ETGUG), and the Dizziness handicap inventory (DHI), were assessed. Results: DVA showed no significant group level change (p = 0.475, z = −0.714, d = 0.295) with a small effect size and improvements in five out of 12 subjects. Ipsilesional VOR gain did not improve (p = 0.157, z = −1.414, d = 0.481) on group level while there was an intermediate effect size and improvements in six out of 12 subjects. COSA got significant smaller (p = 0.006, z = −2.746, d = 1.354) with improvements in seven out of 12 subjects. The contralesional sides did not change. The FGA for the group significantly improved with an intermediate effect size (p < 0.001, z = −3.08, d = 1.617) and five individuals showed clinically relevant improvements. The ETGUG group value improved significantly with a strong effect size (p < 0.001, z = −2.67, d = 1.030), with seven individuals contributing to this change. The DHI showed no change (p = 0.172, z = −1.381, d = 0.592) neither on the group nor on the individuals' level. The game scores of the subjects improved during the intervention period of the intervention for every game. Conclusion: The results of this study demonstrate that exergaming with promoted head turns facilitates vestibular compensation in some subjects with cPVH. This is the first study that shows an improvement in cumulative overt saccade amplitude after exergaming in chronic vestibular subjects.